1996
DOI: 10.3758/bf03201094
|View full text |Cite
|
Sign up to set email alerts
|

Partial matching in the Moses illusion: Response bias not sensitivity

Abstract: Previous research has demonstrated that people have enormous difficultyin detecting distortions in such questions as, "How many animals of each kind did Moses take in the Ark?" Reder and Kusbit (1991) argued that the locus of the effect must be the existence of a partial-match process. Other research has suggested that this partial-match process operates at the word level and that, with adequate focus on the relevant word, the Moses illusion is greatly diminished. The present experimental results argue that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
70
4

Year Published

2000
2000
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(84 citation statements)
references
References 15 publications
10
70
4
Order By: Relevance
“…The source monitoring account suggests that illusory TOTs may be akin to the Moses illusion (Kamas, Reder, & Ayers, 1996).1 In the Moses illusion, participants fail to recognize that an error exists in the question (e.g., How many animals did Moses take on his ark?). Thus, they will often make a response without realizing the error.…”
Section: Discussionmentioning
confidence: 99%
“…The source monitoring account suggests that illusory TOTs may be akin to the Moses illusion (Kamas, Reder, & Ayers, 1996).1 In the Moses illusion, participants fail to recognize that an error exists in the question (e.g., How many animals did Moses take on his ark?). Thus, they will often make a response without realizing the error.…”
Section: Discussionmentioning
confidence: 99%
“…However, task, syntactic structure, sentential focus, instructions, and recent experience all influence the frequency of Moses mistakes (e.g., Bredart & Modolo, 1988;Buyer & Radvansky, 1995;Erickson & Mattson, 1981). For example, if participants first study a relevant fact about Noah (e.g., "Noah took two animals of each kind on the Ark"), they make fewer Moses mistakes (Reder & Kusbit, 1991), and if they learn a misleading association (e.g., "Moses-Ark"), they make more Moses mistakes (Kamas, Reder, & Ayers, 1996;Reder & Cleeremans, 1990;van Oostendorp & Kok, 1990).…”
Section: The Moses Illusion: Current Facts and Theoriesmentioning
confidence: 99%
“…For Moses illusion, there is some evidence that moving the distortion in focus using cleft sentences may actually decrease the illusion rate (Bredart & Modolo, 1988); it is possible that this effect be a position effect, since focused nouns in cleft sentences occur at the beginning of the sentence (e.g., It was Moses who took two animals of each kind on the ark. Bredart and Docquier (1989) also showed that this effect holds when capitalization of the distorted term is used; however, Kamas, Reder, and Ayers (1996) replicated the study and used a bias-sensitivity analysis to prove that capitalization mainly affected participants' bias towards calling a sentence distorted rather than their sensitivity to distortions. Jaarsveld, Dijkstra, and Hermans (1997) investigated position effects on Moses illusion, but, since they did not include an undistorted condition in their experiments, it remains to be shown that their result was indeed an effect of the manipulation.…”
mentioning
confidence: 99%